IMPROVEMENT OF THE TOURISM INFRASTRUCTURE MANAGEMENT SYSTEM OF THE COUNTRY IN THE INTERNATIONAL MARKET - Борблик, Карина (SWorldJournal, 2021)
The work develops a set of measures to create organizational and economic prerequisites for effective information support for sustainable development of the national market of tourist services, a database of market participants, increasing the level of s